Decision making, affect, and learning - Delgado, Mauricio R.; Phelps, Elizabeth A.; Robbins, Trevor W. (Oxford : Oxford University Press, 2011)
This volume focuses on two of the fastest moving research areas in cognitive and affective neuroscience - decision making and emotional processing. It investigates the psychological and neural systems underlying decision making, and the relationship with reward, affect, and learning.
Description based on online resource; title from PDF title page (viewed on May 11, 2011).
Includes bibliographical references and index.
Keywords: Decision making